Exploring migration experiences of foreign footballers to England through the use of autobiographies. (18th August 2022) - Lally, Aaron; Smith, Matt; Parry, Keith D.
ABSTRACT: This article examines the sport labour migration of elite footballers who have transferred from another European country to the English Premier League (EPL). Sport labour migration happens for a number of reasons, including financial gain and professional development. With this, however, comes various challenges like cultural shock and cultural dislocation. To extend the research on migration, data was gathered from autobiographies, with ten premier league footballers who had transferred from one of five selected European leagues. Results revealed a number of insights into a player migratory experience, including the importance of settling in, dealing with the characteristics of a new league, a need for positive support from the club and the negative impact of the media. Findings inform how to improve the migration experiences in both sport and other job sectors that require acculturation.